Comparative Analysis of Steam and Epic Games Store Application Satisfaction Levels Using the Pieces Method - Kusumarini, Cahyawati Diah; Ansi, Caesario Dwinathaly (Review: Journal of Multidisciplinary in Social Sciences, 2025)
Application-based game stores are on the rise recently, so there is a tight gap between Steam and the Epic Games Store. This research provided a description of user satisfaction level towards the two applications and served as a measure of the success of these two applications. The type of research conducted was quantitative research that analyzes data collection from a Likert scale questionnaire instrument. The method used was a descriptive analysis of user satisfaction level on both applications using the PIECES method. This research showed that both applications get satisfaction level results of "Satisfied" category in all variables of the PIECES method. Based on each variable value, the Epic Games Store application was superior to the Steam application. Epic Games Store exceled in four variables, namely Information, Economics, Efficiency, and Service, while the Steam application exceled only in Control & Security variable. Performance variables in both applications got the same value.